Biodiversity and succession of lactic microbiota involved in Brazilian buffalo mozzarella cheese production - Silva, Luana Faria [UNESP]; De Dea Lindner, Juliano; Sunakozawa, Tássila Nakata [UNESP]; Amaral, Daniel Mathias F. [UNESP]; Casella, Tiago; Nogueira, Mara Corrêa Lelles; Penna, Ana Lúcia Barretto [UNESP] (Springer Nature, 2022)
The biodiversity and succession of lactic acid bacteria (LAB) involved in the production and storage of Brazilian buffalo mozzarella cheese were evaluated. The isolates were characterized by Gram staining and catalase test, by the ability to grow at different conditions: temperatures, pH, concentrations of NaCl, and production of CO2 from glucose. The biodiversity and succession of 152 LAB isolated during cheese production were evaluated by 16S rRNA gene sequencing, Random Amplified Polymorphic DNA (RAPD-PCR), and Restriction Fragment Length Polymorphism (RFLP-PCR) techniques. Most of the strains grow well at 30 °C and are tolerant to 6.5% of NaCl, and in general, the best pH for growing was 9.6. Leuconostoc mesenteroides, Lacticaseibacillus casei, Limosilactobacillus fermentum, and Enterococcus sp. were prevalent and present in almost all steps of production. The LAB strains are typically found in the traditional Italian cheese, except the Leuconostoc citreum species. Sixty clusters were obtained by RAPD-PCR with 85% of similarity (114 isolates) while most of the LAB was clustered with 100% of similarity by the RFLP-PCR technique. The applied techniques enabled a valuable elucidation of the LAB biodiversity and succession, contributing to a better understanding of the specific microbial cultures with a technological aptitude of this cheese.
Keywords: Autochthonous bacteria; Cheese biodiversity; Lactic acid bacteria identification; Raw milk